Research progress in graphene based thermal conductivity materials - LI Yue (Journal of Materials Engineering, 2021)
As a two-dimensional(2D) building block of new materials, graphene has received widespread attention due to its exceptional thermal properties. The thermal properties and recent advances on graphene-based material were reviewed. The intrinsic thermal conductivity of graphene and the effect of layers, defects and edge were briefly introduced. The resent research progress in graphene fiber as thermal conductivity material was analyzed and discussed. A variety of graphene films (graphene film, graphene hybrid film, graphene/polymer composite film) were grouped by category and the influencing factors of the thermal conductivity were reviewed. The structure, thermal conductivity property and current researches of 3D graphene (graphene with random orientation in the polymer matrix, graphene with specific orientation in the polymer matrix) were summarized. Finally, the challenges and prospects of graphene-based materials were also pointed out, especially inhigh power, highly integrated systems such as LED lighting and smart phones, graphene based thermal conductivity materials have a good development prospect.